Implementasi Distribusi Pupuk Bersubsidi Di Desa Natambang Roncitan Kecamatan Arse Kabupaten Tapanuli Selatan - Lena Sari Dalimunthe; Humaizi Humaizi; Abdul Kadir (PERSPEKTIF, 2021)
The purpose of this study was to determine the implementation of subsidized fertilizer distribution in the Natambang Roncitan Village, Arse District. This type of research uses qualitative research with descriptive methods. Research informants include the Secretary, Head of Facilities and Infrastructure at the Agriculture Office, Distributors, Retailers, BPP, PPL, and farmer/farmer groups. Data collection techniques using interviews, documentation studies, and data retrieval techniques. The results showed that the implementation of subsidized fertilizer distribution in Natambang Roncitan Village, Arse District was still not optimal due to lack of supervision. Some problems that can still be addressed by the Regional Agriculture Office of South Tapanuli Regency include prices at the farmer/farmer group level that do not match the Highest Retail Price (HET), kiosks that sell to farmers outside their scope of the area, and bureaucracy that is too long in distributing subsidized fertilizers.